I recently discovered a recursive identity for Li−m(z) for m a positive integer. Hopefully this will be of some use when tackling problems seeking for the value of some polylogarithmic sum.
Li−m(z)=1−zz[1+k=0∑m−1(km)Li−k(z)]
Proof:
Consider n=1∑∞zn(n+1)m. We have
n=1∑∞zn(n+1)m=n=1∑∞znk=0∑m(km)nk=n=1∑∞znnm+k=0∑m−1(km)n=1∑∞znnk=Li−m(z)+k=0∑m−1(km)Li−k(z)
We also have
n=1∑∞zn(n+1)m=z1n=2∑∞znnm=z1Li−m(z)−1
Equating the two gives
Li−m(z)+k=0∑m−1(km)Li−k(z)=z1Li−m(z)−1
When rearranged, we obtain
Li−m(z)=1−zz[1+k=0∑m−1(km)Li−k(z)]
as required.
#Calculus
Easy Math Editor
This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.
When posting on Brilliant:
*italics*
or_italics_
**bold**
or__bold__
paragraph 1
paragraph 2
[example link](https://brilliant.org)
> This is a quote
\(
...\)
or\[
...\]
to ensure proper formatting.2 \times 3
2^{34}
a_{i-1}
\frac{2}{3}
\sqrt{2}
\sum_{i=1}^3
\sin \theta
\boxed{123}
Comments
Similarly Li−m(z)=1−z(−1)m[k=0∑m−1(−1)k(km)Li−k(z)]
Log in to reply
Nice!
A point to note is that Li−m(z) , when m is a positive integer, already has a closed form in terms of rational polynomial functions.